Correlation of electron delocalisation with pseudocapacitance in nanostructured carbon - Li, Junfu (2018)
The unique electronic structure - partial electron delocalisation (PED) -has been for the first time correlated with pseudocapacitance in graphene-based electrode materials in this study. Pseudocapacitive charge storage was observed on electrodes fabricated from graphene and related materials with different degrees of electron delocalisation (DED%), including graphene oxide (GO), partially oxidised graphene (POG) and polycrystalline monolayer graphene (PMG). GO working electrodes were electrochemically reduced (ECR) via different potential cycling controls to prepare POGs with different DED%. Raman spectroscopy and X-ray photoelectrons spectroscopy (XPS) were used to qualitatively correlate the DED% with the state of oxidation of GOs. It was found that when the ECR was increased from 0 to 1000 potential cycles, the DED% of GO improved from 12.5% to 60.4%. Electrochemical characterisations were used to monitor the charge storage of ECR-treated GOs, i.e. POGs, in 3.0 M KCl and 1.0 M H2SO4, respectively. Cyclic voltammetry (CV) results showed that as the DED of GO was improved, the specific capacitance (Cm) increased from 0.1 to 38.0 F/g in 3.0 M KCl and 0.2 to 62.0 F/g in 1.0 M H2SO4. Electrochemical impedance spectroscopy (EIS) indicated that the improvement of charge storage could be mainly attributed to pseudocapacitance. In the case of PMG, the CV results showed that the value of Cm was ca. 28.0 F/g in 3.0 M KCl and ca. 64.0 F/g in 3.0 M HCl, respectively, although the DED% of PMG was almost 95.0% as derived from the XPS results. The EIS analyses again indicated that the pseudocapacitive contribution predominated the total charge storage. The electronic structures of representative GO models with DED% varying from 0 to 100% were established based on the density functional theory (DFT) modelling. The results showed that extra electronic states only emerged around the Fermi level of POG species (0% < DED% < 100%), but not in fully oxidised graphene (DED% = 0%), nor in pure graphene (DED% = 100%). These states should have originated from the partially delocalised valence electrons rather than those localised electrons. A non-linear relationship between the charge storage capacity and the DED% was found with a peak at between 65.0 and 75.0% of the DED. Finally, by sorting the specific capacitance of the above mentioned graphene species in the order of their DED%, a non-linear relationship has been found again with a peak between 65.0 to 75.0% of the DED. Both the experimental observations and theoretical predictions have revealed a consistent correlation between the pseudocapacitance and the DED% in graphene oxide electrode materials.